Rynek transportu lotniczego i rozwój infrastruktury w Polsce po akcesji do Unii Europejskiej - Olipra, Łukasz (The Air Transport Market and Infrastructure Development in Poland after Accession to the European Union, 2008)
The article focuses on the air transport market issues in Poland. The article's aim is to answer the question: what changes occurred in the market after Poland's accession to the European Union. The author proposes and tries to defend a thesis that dynamic development of the market is strictly connected with Poland's accession to the EU, and that it imposes then the development of the ground infrastructure. In the first part, the general situation of the world and the EU's civil aviation was presented as background. Then, the Polish air transport market was described. The article contains fact-collecting data concerning: the number of passengers in Poland between 2000 and 2006 in general and in the division into airports, percentage changes of the passengers number, shares of the airports in the market between 2001 and 2006 and shares in market of particular carriers between 2005 and 2006. The last part of the article focuses on the plans of the ground infrastructure development for the years 2007-2013 which were imposed by growing number of passenger carriages and pax operations. The cargo issues were passed over. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 333-344